The macroanatomic investigations on the branches of the femora) artery in the rats - Bumin Emre Teke (Eurasian Journal of Veterinary Sciences)
In this study, the branches of the femoral artery were investigated. For this purpose, five male and five female adult rats were used. Coloured latex was injected to the abdominal aortae. It was seen that, the femoral artery which distal continued of the external iliac artery to the popliteal region from the femoral spatium, branched to the pro-fund lemoral artery, superficial epigastric artery and descending artery between the femoral spatium and popliteal region. Furthermore, it was observed that the popliteal artery and saphenous artery arised from the femoral artery at the popliteal region. It was established that, not to be found the caudal tibial artery in the rats and the caudal branch formed plantar arch at the level proximal phalanxs. It was determined that, the lateral distal genicular artery, lateral proximal genicular artery, medial proximal genicular artery, cranial tibial artery and medial distal genicular artery arised Irom the popliteal artery.